Alpha-PET with terbium-149: evidence and perspectives for radiotheragnostics - Cristina Müller; Christiaan Vermeulen; Ulli Köster; Karl Johnston; Andreas Türler; Roger Schibli; Nicholas P. van der Meulen (SpringerOpen, 2016)
Abstract 149Tb represents a powerful alternative to currently used α-emitters: the relatively short half-life (T1/2 = 4.1 h), low α-energy (3.97 MeV, Iα = 16.7 %), absence of α-emitting daughters and stable coordination via DOTA are favorable features for potential clinical application. In this letter, we wish to highlight the unique characteristics of 149Tb for PET imaging, based on its positron emission (Eβ+mean = 730 keV, Iβ+ = 7.1 %) in addition to it's a therapeutic value. To this end, a preclinical study with a tumor-bearing mouse is presented. The perspective of alpha-PET makes 149Tb highly appealing for radiotheragnostic applications in future clinical trials.